Daisy Petals and Mushroom Clouds : LBJ, Barry Goldwater, and the Ad That Changed American Politics - Mann, Robert, 1958- (Book collections on Project MUSE., 2011)
Thoroughly analyzes the controversial "Daisy Girl" ad run by Lyndon B. Johnson's presidential campaign in 1964, which painted Barry Goldwater as a radical who would lead the United States into nuclear annihilation -- provided by publisher